Resolving Discordant CYP2D6 Genotyping Results in Thai Subjects: Platform Limitations and Novel Haplotypes - Hongkaew, Yaowaluck; Wang, Wendy Y; Gaedigk, Roger; Sukasem, Chonlaphat; Gaedigk, Andrea (Pharmacogenomics, 2021)
Several Luminex xTAG genotype calls were identified as inconsistent or suspicious among Thai subjects and further characterized to identify the root causes. Forty-eight subjects were followed-up with long-range-PCR, quantitative copy number assays and/or Sanger sequencing. Most of the Luminex-duplication calls were either negative or had hybrid structures involving in various configurations. Ten samples were inaccurately called as or alleles. Sequencing revealed three novel haplotypes, and of which two are nonfunctional. The Luminex platform produced a relatively high number of false genotype calls for Thai subjects. Our findings underscore the need for the systematic characterization of the locus in diverse populations and rigorous platform validation.